Rational design of stable sulfur vacancies in molybdenum disulfide for hydrogen evolution - Zhao, Yunxing (2020)
Sulfur (S) vacancies in MoS2 have been found to act as a new active center, which shows an unprecedented intrinsic HER activity under elastic strain. However, such S-vacancies are unstable and the activities are very sensitive to the vacancy concentration. A strategy to stabilize these abundant active sites is thus highly desirable. Herein, we rationally design a catalyst system to stabilize S-vacancies in the basal plane of 2H-MoS2 supported on defective vertical graphene network (VGN). The energetically favorable line-shaped S-vacancies in MoS2 show a consistently high HER activity that is insensitive to S-vacancy concentration. Moreover, the defective graphene support effectively stabilizes these S-vacancies. The optimized catalyst exhibits a superior HER activity with overpotential of 128 mV at 10 mA cm−2 and Tafel slope of 50 mV dec−1. Most importantly, the catalyst shows greatly increased stability over 500 h; benchmarking the most stable nonprecious HER catalyst in acidic media to date.